Taxonomizing Building Forms and Characteristics for Urban Scale Virtual Reality 3D Models - Idrawani Zaini, Atta; Rose Amer Koesmeri, Dona; Nur Syaheeza Raja Mohd Yazit, Raja; ., . (International Journal of Engineering and Technology, 2019)
Virtual reality (VR) technology allows urban environments to be experienced through a full-scale digital immersion. However, as the virtual environment (VE) in VR is set to be in full-scale by default, what can be considered as adequate details for architectural operations in large VEs is therefore ambiguous. This paper aimed to taxonomize building forms and characteristics represented as level of details (LOD) in creating operational urban scale 3D models for VR. A total of N=96 respondents participated in a survey, in which they were requested to rank the building characteristics critical to be represented in an urban scale VE. A Principal Component Analysis (PCA) was then used to factorize these characteristics which resulted to ‘geometric extrusion’ and ‘distinction’. These components were then used to define the taxonomy of urban scale 3D models for VR.